Peningkatan Kemampuan Fotografi Produk Menggunakan Smartphone Pada UMKM Gunusa (Gunungkidul Usaha) - Dhimas Adi Satria (Universitas Muria Kudus, 2023)
The development of the world of photography today is very rapid and has become a very important need in human daily life. The diversity of social media is a means of appreciating and publishing photography or images. So that there are many opportunities that can be obtained from the diversity of social media for the development of photography, one of which is photography is used as a marketing medium for a product. Product photos are one of the factors that support whether the product looks attractive or not when it is promoted on social media. GUNUSA or (Gunungkidul Usaha) is a Micro, Small and Medium Enterprise (UMKM) that covers all areas in Wonosari, Gunungkidul Yogyakarta. Where the people who are members of this group are small regional community groups that have products that have high selling value. However, understanding of techniques and the use of product photos as promotional needs is still hindered by expensive and sophisticated equipment, besides that, community resources in the area are still rarely knowledgeable about the use of product photos. For this reason, to meet the needs of Gunusa, it is necessary to provide assistance and training on product photography techniques in the form of introduction to theory, practice on location, and product photo trials with media from each business field of UMKM participants, it is hoped that by using Smartphones as a cheap photography tool. and easy to find can increase marketing on social media